A proposed application of Monte Carlo method in teaching probability - Kolková, Mária; Pócsová, Jana; Šveda, Dušan (Teaching Mathematics and Computer Science, 2012)
Pupils' misconception of probability often results from lack of experience. Combining the concept of probability and statistics, the proposed application is intended for the teachers of mathematics at an elementary school. By reformulating the task in the form of an adventure, pupils examine a mathematical problem, which is too difficult for them to solve by combinatorial method. By recommending the simulation of the problem, we have sought to provide pupils with valuable experience of experimenting, recording and evaluating data.